Functional magnetic resonance imaging study on dysphagia after unilateral hemispheric stroke: a preliminary study. Issue 12 (9th June 2009) - Li, S; Luo, C; Yu, B; Yan, B; Gong, Q; He, C; He, L; Huang, X; Yao, D; Lui, S; Tang, H; Chen, Q; et al.
Abstract : Background: Swallowing dysfunction is common and disabling after acute stroke; however, the mechanism of dysphagia or recovery of swallowing from dysphagia remains uncertain. The purpose of this study was to explore cerebral activation of swallowing in dysphagia using functional MRI (fMRI) to compare the functional anatomy of swallowing in unilateral hemispheric stroke patients and healthy adults. Methods: In total, five left hemispheric stroke patients with dysphagia, five right hemispheric stroke patients with dysphagia and 10 healthy controls were examined with event related fMRI while laryngeal swallow related movements were recorded. Data were processed using the general linear model. Results: A multifocal cerebral representation of swallowing was identified predominantly in the left hemisphere, in a bilateral and asymmetrical manner. Cerebral activation during swallowing tasks was localised to the precentral, postcentral and anterior cingulate gyri, insula and thalamus in all groups. Activation of volitional swallowing in dysphagic unilateral hemispheric stroke patients might require reorganisation of the dominant hemispheric motor cortex, or a compensatory shift in activation to unaffected areas of the hemisphere. Conclusions: The results indicate that unilateral stroke of either cerebral hemisphere can produce dysphagia. Effective recovery is associated with cerebral activation related to cortical swallowing representation in the compensating or recruited areas of the intact hemisphere. Functional MRI is a useful method for exploring the spatial localisation of changes in neuronal activity during tasks that may be related to recovery. Therefore, the subsequent information gleaned from changes in neural plasticity could be useful for assessing the prognosis of dysphagic stroke.